TINJAUAN YURIDIS TRADISI ADAT MANDI PENGANTIN (BAPAPAI) ADAT DAYAK BAKUMPAI DI BANDAR KARYA KECAMATAN TABUKAN MARABAHAN DALAM PERSFEKTIF HUKUM ADAT - Maria Ulfah; Sri Herlina; Munajah Munajah (Fakultas Hukum, Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2023)
Dayak Bakumpai traditional marriage in the traditional bridal shower (bapapai) tradition in Bandar Karya, Tabukan Marabahan sub-district in the Perspective of Customary Law in the form of bridal showers which are usually held in the front yard of the house and become a spectacle for residents. This research is empirical legal research, which means legal research that functions to see the law realistically and examine how the law works in society. The type of this research is descriptive research, where the descriptive method is used in researching the status of a group of people, an object, a condition, or a system of thought or events in the present. The bapapai tradition is an obligation that must be carried out by the bride and groom the day before the wedding celebration. In practice uses various kinds of tools and materials and contains philosophical meaning. This tradition seeks protection from Allah SWT to avoid disturbance by spirits during wedding celebrations and in household life. Society's view of the Dayak Bakumpai traditional marriage in the traditional bridal shower (bapapai) tradition in Bandar Karya, Tabukan Marabahan sub-district, is a marriage that leads to efforts to continue offspring. In contrast, the social structure leads to traditional or customary societal institutions. The procession of carrying out the bridal shower (bapapai) in the bandarkarya sub-district tabukan marabahan in the Customary Law Perspective among the adat bakumpai because the cultural procession of marriage is maintained as a norm of togetherness by each tribe. Every implementation of traditional marriages, traditional events that are carried out can be seen as a form of community education. Custom is part of the culture that determines human values. The marriage tradition in the Bakumpai Dayak Tribe is a hereditary custom passed down so that it is inherent in the Bakumpai Dayak community in the Tabukan Marabahan sub-district.